Vil Du?! incorporation of a serious game in therapy for sexually abused children and adolescents - Joyce J. Endendijk; Henny K. Tichelaar; Menno Deen; Maja Deković (BMC, 2021)
Abstract Background Talking about experiences of sexual abuse in therapy is difficult for children and adolescents, amongst others due to a lack of vocabulary to describe the situation, avoidance, or feelings of shame, fear, and self-blame. The serious game Vil Du?! was developed to help children open up about sexual experiences. Vil Du?! is a non-verbal communication game, which resembles a dress-up game, in which children can show the therapist what happened to them. The current study examined how and for which therapy components Vil Du?! was used by therapists. Methods We used a mixed-methods triangulation design. Therapists filled out online surveys about the use of Vil Du?! with 23 clients (M age = 11.38 years, SD = 3.96; 61 % female). We also conducted semi-structured interviews with 10 therapists. The data were analyzed in SPSS (quantitative) and Nvivo (qualitative) following the stepwise guidelines of Zhang and Wildemuth. Results Merged qualitative and quantitative data revealed that therapists acknowledged the usefulness of Vil Du?! mostly for the therapy components trauma narration and processing, and psycho-education about sexuality. In addition, Vil Du?! might be most useful for clients who have difficulty with disclosing sexual abuse experiences, due to limited verbal abilities or feelings of guilt, shame, avoidance, and tension. Conclusions Recommendations from this study were incorporated in a user manual as a first step toward more systematic and broad implementation of Vil Du?! in the treatment of young sexual abuse victims. A next step is to test whether implementing Vil Du?! in therapy is effective in reducing the negative mental health consequences of sexual abuse for children and adolescents.